2010
DOI: 10.1124/jpet.110.171108
|View full text |Cite
|
Sign up to set email alerts
|

The Anticonvulsive Drug Lamotrigine Blocks Neuronal α4β2 Nicotinic Acetylcholine Receptors

Abstract: Lamotrigine (LTG), an anticonvulsive drug, is often used for the treatment of a variety of epilepsies. In addition to block of sodium channels, LTG may act on other targets to exert its antiepileptic effect. In the present study, we evaluated the effects of LTG on neuronal nicotinic acetylcholine receptors (nAChRs) using the patch-clamp technique on human ␣4␤2-nAChRs heterologously expressed in the SH-EP1 cell line and on native ␣4␤2-nAChRs in dopaminergic (DA) neurons in rat ventral tegmental area (VTA). In S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 36 publications
(57 reference statements)
0
24
0
Order By: Relevance
“…In addition, lamotrigine has weak inhibitory effects at the 5-HT 3 , 5-HT 1A , and nicotinic acetylcholine receptors (Bourin et al, 2005; Zheng et al, 2010). Although not approved to treat schizophrenia, clinical studies have noted lamotrigine may improve some symptoms in a clozapine-resistant patient population (Goff, 2009; Tiihonen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lamotrigine has weak inhibitory effects at the 5-HT 3 , 5-HT 1A , and nicotinic acetylcholine receptors (Bourin et al, 2005; Zheng et al, 2010). Although not approved to treat schizophrenia, clinical studies have noted lamotrigine may improve some symptoms in a clozapine-resistant patient population (Goff, 2009; Tiihonen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The nicotine-induced maximal current was also reduced in the presence of lamotrigine (Zheng et al, 2010). In freshly dissociated ventral tegmental area dopaminergic neurons, lamotrigine inhibited α 4 β 2 nAChRs-mediated currents but did not affect glutamate-or GABA-induced currents, indicating that lamotrigine selectively inhibits α 4 β 2 nAChR function (Zheng et al, 2010). These data may raise the possibility that lamotrigine could be beneficial in the treatment of seizures in ADNFLE.…”
Section: Lamotriginementioning
confidence: 92%
“…Using the patch-clamp technique on human α 4 β 2 nAChRs heterologously expressed in the SH-EP1 cell line and on native α 4 β 2 nAChRs in dopaminergic neurons in rat ventral tegmental area, Zheng et al (2010) have recently revealed that lamotrigine is able to diminish the peak and steadystate components of the inward α 4 β 2 nAChR-mediated currents in a concentration-, voltage-, and use-dependent manner. The nicotine-induced maximal current was also reduced in the presence of lamotrigine (Zheng et al, 2010). In freshly dissociated ventral tegmental area dopaminergic neurons, lamotrigine inhibited α 4 β 2 nAChRs-mediated currents but did not affect glutamate-or GABA-induced currents, indicating that lamotrigine selectively inhibits α 4 β 2 nAChR function (Zheng et al, 2010).…”
Section: Lamotriginementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies further suggested that the neuronal α4β2-nAChR (neuronal nicotinic acetylcholine receptor) is likely an important target. The blockade of α4β2-nAChR might represent the mechanism through which LTG effectively controls some types of epilepsy such as autosomal dominant nocturnal frontal lobe epilepsy or juvenile myoclonic epilepsy (27). Among the adverse effects, idiosyncratic drug reactions, especially skin rashes are considered fatal and may require discontinuation of the drug.…”
Section: Antiepileptic Drugs (Structures See Figure 2)mentioning
confidence: 99%